Green space water use and its impact on water resources in the capital region of China. (October 2017) - Zhang, Xuanchang; Mi, Feng; Lu, Nan; Yan, Nana; Kuglerova, Lenka; Yuan, Shibao; Peng, Qiang; Ma, Oliver Zheyi
Abstract: Green space plays important roles in the environment as an integral part of the urban ecosystem. It may have various impacts on urban water resources depending on its location and type. Beijing is a major city that is severely deficient in water resources and the conflicts of water demand between different users such as industry, farm, residence, orchard, etc., becoming increasingly evident. Thus rational water utilization within the green space is critical to regional water security. Based on remote sensing, field investigation, and statistical data, this study focuses on the water use and the impacts of three types of green space (i.e., mountainous vegetation, suburban farmland, and green gardens) on water resources in the capital region of China from 2002 to 2013. The results show that the mean annual evapotranspiration (ET) was around 600 mm for the mountainous vegetation, which is almost equal to precipitation (P) in normal years. However, in the years with elevated rainfall, the mountainous vegetation distributing in catchment region contributed water to the reservoirs. In contrast, suburban farmland and green gardens were both dependent on groundwater for irrigation, with the rainfall utilization rate being low, which caused negative effects on water resources. The inefficient irrigation of suburban farmland was up to 115 mm and the suburban farmland area with higher water consumption was 230 km 2 in 2005 (out of the total 50% suburban farmland). ET of the green gardens was relatively low (400 mm) compared to the mountainous vegetation. P (525 mm) could meet the demand of ET, and consequently, irrigation (as high as 581.95 mm/m 2 ) was actually superfluous. Our results suggest that an integrated water management scheme is needed for the green space, this includes improving irrigation efficiency and increasing infiltration rate of rainfall in urban land surface. Highlights: Different types of green space have different impacts on urban water resources and ecosystem. The mountainous vegetation plays important roles in regulating annual water flow. The inefficient irrigation in suburban farmland and green gardens have negative effects on water resources.